On the W. Fucks’s distribution law for the formation of linguistical elements - Merkytė, R.; Kalinka, V. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Мерките, В.Калинка. К закону образования лингвистических элементов В. ФуксаR. Merkytė, V. Kalinka. Apie V. Fukso dėsnį kalbos elementams tirti